At the crossroads of calcium signaling, protein synthesis and neuropeptide release - Jakob Rupert; Dragomir Milovanovic (eLife)
By influencing calcium homeostasis, local protein synthesis and the endoplasmic reticulum, a small protein called Rab10 emerges as a crucial cytoplasmic regulator of neuropeptide secretion.